2020
DOI: 10.1186/s13071-020-04486-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of antimony resistant and susceptible Leishmania infantum lines

Abstract: Background One of the major challenges to leishmaniasis treatment is the emergence of parasites resistant to antimony. To study differentially expressed genes associated with drug resistance, we performed a comparative transcriptomic analysis between wild-type and potassium antimonyl tartrate (SbIII)-resistant Leishmania infantum lines using high-throughput RNA sequencing. Methods All the cDNA libraries were constructed from promastigote forms of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 82 publications
3
24
0
Order By: Relevance
“…The LiSbR line showed an upregulation of thirty-seven transcripts belonging to the protein phosphorylation category, which includes a DUSP that was 8.93fold upregulated. In addition, a PPP and a PP2C were 2.28-to 17.52-fold upregulated, respectively (Andrade et al, 2020). This is consistent with a previous proteomic analysis that found a major abundance of both enzymes in the Sb III -resistant line (Matrangolo et al, 2013).…”
Section: Differential Expression Of Phosphatases In Drug-resistant Parasitessupporting
confidence: 91%
See 2 more Smart Citations
“…The LiSbR line showed an upregulation of thirty-seven transcripts belonging to the protein phosphorylation category, which includes a DUSP that was 8.93fold upregulated. In addition, a PPP and a PP2C were 2.28-to 17.52-fold upregulated, respectively (Andrade et al, 2020). This is consistent with a previous proteomic analysis that found a major abundance of both enzymes in the Sb III -resistant line (Matrangolo et al, 2013).…”
Section: Differential Expression Of Phosphatases In Drug-resistant Parasitessupporting
confidence: 91%
“…While STPs and PTPs are related to cell signaling (Saxena et al, 2007;Dillon et al, 2015;Alcolea et al, 2016), membrane-bound HAcPs seem to play a role in the response to protein recycling during stress conditions, such as nutrient starvation (Martin et al, 2014;Inbar et al, 2017). Leishmania phosphatases are also upregulated in drug-resistant strains (Matrangolo et al, 2013;Bhandari et al, 2014;Verma et al, 2017;Patino et al, 2019;Andrade et al, 2020). STPs may contribute to parasite resistance by activating ABC transporters, leading to an increase in drug efflux (Bhandari et al, 2014;Verma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic and genomic analyses of Sb IIIresistant L. infantum mutants identified MRPA as a biomarker and suggested the involvement of chromosome number variations, specific gene amplifications, and SNPs as important features of antimony resistance (Brotherton et al, 2013). The transcriptomic profile showed that many pathways upregulated in L. infantum antimony-resistant lines are associated with protein phosphorylation, microtubule-based movement, protein ubiquitination, stress response, regulation of membrane lipid distribution, proteins involved in RNA metabolism, and other important metabolic pathways (Andrade et al, 2020). Together, these results show that the mechanism of antimony-resistance in Leishmania is complex and multifactorial, identifying several candidate genes that may be further evaluated as molecular targets for chemotherapy of leishmaniasis.…”
Section: Pentavalent Antimonialsmentioning
confidence: 99%
“…One possible approach is the integration of public available RNAseq data depicting the resistance phenomena in gene regulatory networks (Andrade et al, 2020). Such approach has demonstrated how genes interact with each other and how changes in their expression levels may result, for example, in different immunological responses promoting distinct disease outcomes including leishmaniasis (Mol et al, 2018).…”
Section: Leishmania Systems Biologymentioning
confidence: 99%